UMPSA ‘Ziarah Prihatin’ provides early education assistance to its prospective students - Naqiah, Puaad (UMPSA, 2024)
KUANTAN, 25 July 2024 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) is dedicated to assisting prospective foundation and diploma students as they prepare to begin their studies at UMPSA.